THE INFLUENCE OF LEARNING MOTIVATION AND LEARNING READINESS ON THE LEARNING OUTCOMES OF ACCOUNTING STUDENTS AT SMK NEGERI TATAPAANS - Fresilia Mamengko; Sjeddie Rianne Watung; Jerry R. H. Wuisang (Program Studi Pendidikan Bahasa Inggris, 2025)
Learning motivation and readiness are essential factors that determine the success of the educational process. In modern education, students’ academic achievements are often influenced not only by teaching methods but also by their internal drive and preparedness to learn. However, many students still face challenges in maintaining high motivation and sufficient readiness, which creates a gap between expected learning outcomes and actual academic performance. Therefore, this study aims to determine the influence of learning motivation and learning readiness on students’ learning outcomes. This research employs a quantitative approach using multiple regression analysis to examine how both factors contribute to learning performance. Data were collected through questionnaires distributed to students at the secondary education level and analyzed using statistical software to identify relationships and significance among variables. The results reveal that learning motivation and learning readiness have a positive and significant effect on students’ learning outcomes. The strong relationship between these independent variables and academic performance indicates that the higher the students’ motivation and readiness, the better their learning results. In conclusion, the findings highlight that improving students’ academic success requires not only effective teaching strategies but also the enhancement of students’ internal motivation and preparedness. Thus, teachers and schools are encouraged to build a supportive and stimulating learning environment that fosters both motivation and readiness for optimal learning outcomes.